Viable Strategies to Increase Clinical Trial Patient Diversity - Brathwaite, Justin; Wolgast, Marley; Bickhart, Sara (AL-Kindy College Medical Journal, 2023)
In the United States, the pharmaceutical industry is actively devising strategies to improve the diversity of clinical trial participants. These efforts stem from a plethora of evidence indicating that various ethnic groups respond differently to a given treatment. Thus, increasing the diversity of trial participants would not only provide more robust and representative trial data but also lead to safer and more effective therapies. Further diversifying trial participants appear straightforward, but it is a complex process requiring feedback from multiple stakeholders such as pharmaceutical sponsors, regulators, community leaders, and research sites. Therefore, the objective of this paper is to describe three viable strategies that can possibly increase the diversity of clinical trial participants: (1) Diversification of the clinical research workforce. (2) Adoption of the diversity in site assessment tool, and (3) incorporation of decentralized clinical trial technologies into clinical trial designs.